QS. Al-W?qi‘ah: 75–80 dalam Perspektif Teori Tarjamah Modern: Integrasi Konseptual Antara Equivalence dan Skopos dalam Pemaknaan Teks Sakral: Pendahuluan, Landasan Teori, Metode, Hasil dan Pembahasan, Kesimpulan dan Penutup - Khansa Tsabitah; Zahra Aurelia; Toto Edidarmo; Fadhil Putera Jazuli; Naufal Widad (Universitas KH. Mukhtar Syafaat, 2026)
This study analyzes the Indonesian translation of verses 75–80 from Surah Al-W?qi‘ah through the perspective of interpretative translation. The research aims to examine how symbolic and rhetorical meanings in the Qur’anic text are conveyed into the target language while maintaining the essence of the original message. Using a descriptive-analytical method, the researchers examined the Indonesian translation issued by the Ministry of Religious Affairs in comparison with the Arabic source text. The findings reveal that the translation goes beyond literal rendering, employing an interpretative approach to communicate deep concepts such as divine oath, sacredness, and revelation. The study concludes that applying interpretative translation in this context enhances the audience’s comprehension and connects the message to the local cultural framework.